A Comparative Study between Thoracic Epidural Anesthesia and General Anesthesia for Patients Who Underwent Modified Radical Mastectomy with Axillary Lymph Node Dissection in De La Salle University Medical Center - Eva Oktavia (The Prodia Education and Research Institute (PERI), 2015)
BACKGROUND: To compare the recovery time and other related clinical outcomes among patients who underwent Modified Radical Mastectomy (MRM) with axillary lymph node dissection under Continuous Thoracic Epidural Anesthesia (CTEA) and General Endotracheal Tube Anesthesia (GETA).METHODS: A retrospective cross-sectional study with 70 patients who underwent MRM in De La Salle University Medical Centre (DLSUMC), categorized into GETA and CTEA group consisted of 35 patients each. Per oral premedications 15 mg midazolam, 40 mg omeprazole and 10 mg metoclopramide were given 1 hour prior to surgery. Intra-operative hypotension/hypertension, tachycardia/bradycardia status, length of Post-Anesthesia Care Unit (PACU) and hospital stay, and Post Operative Nausa and Vomiting (PONV) incidence were compared between 2 groups.RESULTS: Preoperatively, there were no significant differences between the groups in terms of subject characteristic. Intra-operatively, hypertension was more frequent in GETA group (28.6% vs. 0%), while hypotension was more frequent in the CTEA (80% vs. 57.1%). Tachycardia was more frequent in GETA group (46.6% vs. 0%), meanwhile bradycardia was more frequent in CTEA (40% vs. 17.1%). Postoperatively, the GETA group had shorter PACU stay than CTEA (230 mins vs. 267 mins), but CTEA group had a shorter time of hospital stay compared to GETA (58.1 hours vs. 67.7 hours). The incidence of PONV were comparable among the two groups (GETA 46.7% vs. CTEA 50%). Statistically there were no significant differences between the two groups in all of the above characteristics.CONCLUSION: CTEA technique has no effect on inducing hypertension and tachycardia, but hypotension and bradycardia may occur. Although GETA gives shorter PACU duration, CTEA gives shorter hospital stay. This gave impression that CTEA is an effective alternative technique to GETA in patients who underwent MRM with axillary dissection.KEYWORDS: modified radical mastectomy, general anesthesia, epidural anesthesia